Microfinance services for smallholder farmers: An assessment from rice farmers' expectations in Central Benin - Smith A. R. Dossou; Augustin K. N. Aoudji; Albertine M. Houessou; Rodrigue S. Kaki (Agricultural and Food Economics, 2020)
This study analyzed the adequacy between credit supply and the expectations of rice farmers in Central Benin to define policies for improved agricultural-oriented financial services. A survey was conducted in October 2016 among 120 rice farmers randomly selected from six rice-farming villages. Data collected through structured and semi-structured interviews included the financial services offered by Microfinance Institutions, socio-demographic characteristics of rice farmers, their expectations and perception. Multivariate analysis combining hierarchical ascending cluster analysis and principal component analysis (PCA) was used to define the distinct groups of rice farmers according to their credit expectations. The unmet expectations of rice farmers for a credit scheme that suits their needs were identified based on the gaps between their expectations and perception. There were three rice farmers' clusters with distinct characteristics based on their expectations. These farmers were not satisfied with all the attributes of the current credit scheme. Pending the effectiveness of the agricultural bank, the approaches such as the inventory credit system are useful in facilitating credit access to smallholder farmers. It is also essential to combine credit supply with financial education and technical support in a system such as contract farming.
Keywords: 330; Credit access; Rice farming; Expectations; Perception; Benin